2016
DOI: 10.21275/v5i3.nov162015
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of IgM Antibodies to Dengue Fever Virus among Patients Presenting with Symptoms of Fever in Some Hospitals in Kaduna State, Nigeria

Abstract: Dengue fever is a viral infection that has become a major public health concern. The research was aimed at determining the seroprevalence of dengue fever virus by screening for IgM antibodies against the virus. A cross sectional study was carried out in three selected Local government Areas (Zaria, Kafanchan, and Birnin-Gwari Local) of the three senatorial district of Kaduna state, Nigeria from October to December 2014. A total of 366 patients presenting with symptoms of fever were recruited and about 5mls of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(6 reference statements)
1
2
1
Order By: Relevance
“…Of the 956 dengue-suspected patients examined in this study, we found 118 dengue positive cases. The number of males and females infected was equal, contrasting the results of earlier reports, where female preponderance was observed (16)(17)(18)(19). This observation also contrasts with other studies that found a higher rate of dengue infection among males (20)(21)(22).…”
Section: Discussioncontrasting
confidence: 96%
“…Of the 956 dengue-suspected patients examined in this study, we found 118 dengue positive cases. The number of males and females infected was equal, contrasting the results of earlier reports, where female preponderance was observed (16)(17)(18)(19). This observation also contrasts with other studies that found a higher rate of dengue infection among males (20)(21)(22).…”
Section: Discussioncontrasting
confidence: 96%
“…Again, in India, [15] the seroprevalence was 24.9% among febrile patients of which males were twice more affected than females. A higher female than male seroprevalence was however reported in Nigeria [16] [17], which was also similar to this study. The variability in gender prevalence could be ascribed to exposure to Aedes aegypti due to occupational differences that might affect their exposure time to the mosquitoes.…”
Section: Discussionsupporting
confidence: 91%
“…When symptomatic, exposure to alphavirus or flavivirus infections often exhibits as a self-limiting, acute febrile illness with a wide range of mild to severe symptoms. These symptoms, many which mimic malaria, may include fever, joint pain, joint swelling, headache, muscular pain, rash, and mild bleeding [ 14 , 15 ]. In Nigeria, malaria parasites transmitted by Anopheles mosquitoes have been previously reported to be co-circulating with arboviruses, with many infected individuals presenting co-infection of malaria parasites ( Plasmodium falciparum and Plasmodium vivax) with an arboviral infection [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria is endemic for many arboviruses, including DENV, CHIKV, WNV, yellow fever virus (YFV), and Rift Valley fever virus (RVFV); however, many outbreaks go undocumented, and the true burden of endemicity remains undetermined due to lack of systematic studies, limited data, insufficient diagnostic capabilities, and misdiagnosis as malaria [ 14 , 15 , 16 , 17 , 21 , 22 ]. The goal of the present study is to further the understanding of the seroprevalence and risk factors associated with flavivirus and alphavirus infections among individuals from three major population centers in Nigeria.…”
Section: Introductionmentioning
confidence: 99%